(untitled) (Journal of Statistics on Health Decision, 2021)
COVID-19 is an infectious disease caused by the SARS-CoV-2 virus that emerged in China and has since spread rapidly to all countries in the world. The aim of this study is to characterize the peak of the first wave of the pandemic using some demographic and clinical determinants. The database studied contains epidemiological surveillance data of COVID-19 from Portugal until June 30, 2020. The peak of the pandemic was determined considering the number of diagnoses, deaths, and hospitalizations over time, and the estimated period for the first wave was between March 19 and April 24. Logistic regression models were performed to estimate the univariate and multivariate Odds Ratio (OR) and the respective 95% confidence intervals (95% CI) for this period and for each of the variables considered in relation to both study outcomes: mortality (5.8%) and hospitalization (18.8%). The main risk factors considered for the mortality outcome were: Age Group (≥ 80 years: OR = 11.978; 65-79 years: OR = 4.064; Ref. G.: <64 years:), Hospitalization (OR = 6.479) and Comorbidities (OR = 5.735). For the outcome hospitalization, the main risk factors were: Age Group (≥ 80 years: OR = 8.537; 65-79 years: OR = 3.899; Ref. G.: <64 years), male gender (OR= 1.575) and Comorbidities (OR = 5.193). The proposed models presented high area under curves (AUC) results (mortality: AUC=91.05%; and hospitalization: AUC=84.5%), with small amplitudes in the 95% CI. The present study demonstrated that, overall, the major risk factors associated with worse prognostics of COVID-19 were advanced age (over 65 years), and the existence of comorbidities. For the risk of hospitalizations, the male gender was also a significant risk factor.